Kontestasi Penafsiran Ayat Teologi di Ruang Digital: Analisis Komparatif Tafsir Audiovisual Surat Al-Baqarah ayat 115 Oleh Musthafa Umar dan Firanda Andirja di Kanal YouTube - Ananta, Pramudia; Masruro, Uliyatul; Sholihah, Safiratus; Amru, Khobiru (UIN Sultan Syarif Kasim Riau, 2023)
The interpretation of theological verses in the context of digital space has become an interesting phenomenon to study, considering its challenges and risks, such as the potential for inaccurate or extreme interpretations to be disseminated. Therefore, it is crucial to remain critical and verify the sources of information used in the interpretation of theological verses. This research aims to conduct a comparative analysis of the audiovisual interpretation of Surah al-Baqarah verse 115 by Musthafa Umar and Firanda Andirja on YouTube channels. This verse holds significant relevance in Islamic teachings, particularly concerning the principle of Tawhid (the oneness of God) and the change of the Qiblah direction in prayer worship. The research uses a descriptive qualitative method with a comparative analysis approach. The focus of this research is on the differences and similarities in the approaches and explanations between Musthafa Umar and Firanda Andirja in interpreting the theological verse. Data sources were obtained from their respective audiovisual interpretations delivered through the YouTube channels